Supernumerary bilateral tooth germs mimicking radiolucent bone pathology - Flores, Isadora Luana; Mahon, Natanael de Alencar Samarcos; Gamba, Thiago de Oliveira; Assis, Afonso Celso; Gomes, Ana Paula Neutzling; Lopes, Sérgio Lúcio Pereira de Castro (Journal of Oral Diagnosis, 2017)
The immature tissues of teeth germs may mimicking odontogenic and non-odontogenic lesions. About this, an asymptomatic bilateral well-circumscribed radiolucency found during the routine evaluation is considered an uncommon finding and both supernumerary and maxillomandibular bone pathologies should be listed. Quite often, it is one clinical exercise to suggest diagnostic hypotheses to unspecific radiolucency image since cysts, neoplasms and dental anomalies are possible. Here, we reported a case of bilateral supernumerary teeth germs in a 12-years-old Caucasian patient highly suspicious of bone pathology due to completely radiolucent aspect. So, this is the first article to presents a case of bilateral teeth germs as an alert to early stage of tooth crypts in the differential diagnosis of mandibular circumscribed radiolucencies.